Tracking hydration status changes by bioimpedance spectroscopy in children on peritoneal dialysis. Issue 2 (March 2021) - Karava, Vasiliki; Stabouli, Stella; Dotis, John; Liakopoulos, Vassilios; Papachristou, Fotios; Printza, Nikoleta
Background: This 6-month prospective longitudinal study investigates the association between hydration status changes using bioimpedance spectroscopy (BIS) and systolic blood pressure (SBP), pulse pressure (PP), and serum albumin (sAlb) changes in children on peritoneal dialysis (PD). Methods: Thirteen patients (median age: 12.58 years) were enrolled. Normal hydration, moderate hydration, severe overhydration, and dehydration were defined as −7% ≤ relative overhydration (Re-OH) < +7%, +7% ≤ Re-OH < +15%, Re-OH ≥ +15%, and Re-OH < −7%, respectively. Automated office blood pressure z -score, sAlb, and weight z -score were recorded. Results: Fifty-two Re-OH measurements were recorded: three in five, four in five, five in two, and seven in one patient, respectively. SBP was higher and sAlb lower in cases with severe overhydration (9 readings) ( p < 0.001, p < 0.001), but distribution of these parameters did not differ between normal hydration/dehydration (28 readings) and moderate overhydration (15 readings) cases. In patients with hydration status change, SBP and PP were higher while sAlb lower in cases with higher hydration status level ( p = 0.026, p = 0.05, and p = 0.109, respectively). In all patients, visit-to-visit SBP, PP, and sAlb changes were correlated to Re-OH changes ( r s = 0.693, p < 0.001; r s = 0.643, p < 0.001; r s = −0.444, p = 0.008, respectively) but not to weight changes ( r s = 0.052, p = 0.754; r s = 0.034, p = 0.838; r s = −0.156, p = 0.378, respectively). Visit-to-visit Re-OH changes, which were >+4% or <−4%, were linearly correlated to SBP ( r = 0.858, p < 0.001), PP ( r = 0.757, p < 0.001), and sAlb ( r = −0.699, p = 0.002) changes. Conclusion: In children on PD, longitudinal Re-OH changes are superior to weight changes in assessing volume-dependent variations of SBP, PP, and sAlb. Routine BIS application, rather than single BIS measurements, seems useful in the intra-patient monitoring of hydration status.